Picazoplatin, an Azide-Containing Platinum(II) Derivative for Target Analysis by Click Chemistry - White, Jonathan D. (2013)
Despite the broad use of platinum-based chemotherapeutics, identification of their full range of cellular targets remains a significant challenge. In order to identify, visualize, and isolate cellular targets of Pt(II) complexes, we have modified the chemotherapeutic drug picoplatin with an azide moiety for subsequent click reactivity. The new compound picazoplatin readily binds DNA and RNA oligonucleo-tides and undergoes facile post-labeling click reactions to alkyne-fluorophore conjugates. Pt-fluorophore click reactions in ribosomal RNA purified from drug-treated S. cerevisiae demonstrate its potential for future in vivo efforts.